Visual Novel Authoring Tool Berbasis Web - Admaja, Hans Aditya; Andjarwirawan, Justinus; Purba, Kristo Radion (Jurnal Infra, 2015)
Visual Novel is an interactive fiction game comprised of static images, sounds, and video combined. However, almost all of visual novel available are only accessible after completing the installation process on the platform defined by the development of that visual novel. Besides, authoring tools specialized for visual novel making are mainly based on desktop. Through this development, the authors would like to provide a widely accessible application which is available over the web and delivering ease of use of visual novel authoring tool. Availability of playable visual novel is also included to be one advantage of playing visual novel hassle-free.The results obtained from this application, among others, can upload and manage files necessary to be used in the visual novel project as its resource, create a visual novel through the provided editor, publish created visual novel, and play all published visual novel.